Effect of E-Government Services on Performance of Nigeria Immigration Service, Adamawa State Command, Nigeria - Lawan Titus Cosmas (JOURNAL OF PUBLIC ADMINISTRATION AND SOCIAL WELFARE RESEARCH, 2026)
This study examined the effect of e-government services on the performance of the Nigeria Immigration Service (NIS) in Adamawa State. A cross-sectional research design was adopted to obtain data from both service providers and service users. The target population comprised 310 NIS personnel and 75,926 service users, giving a total population of 76,236. Using Yamane’s (1967) formula at a 5% level of precision, a sample size of 398 was determined, and an additional 10% was added to account for non-response, resulting in 438 respondents. Data were collected through structured questionnaires, while secondary data were sourced from official reports, policy documents, and academic literature. Instrument reliability was confirmed using Cronbach’s Alpha with a threshold of 0.70. Quantitative data were analyzed using descriptive statistics, Pearson correlation, and multiple regression analysis with SPSS version 26. The findings revealed that e-government services significantly and positively influence the performance of the NIS. Online service delivery improved accessibility and operational efficiency (β = 0.155, p < 0.05). Electronic document processing had a strong positive effect on performance by enhancing accuracy, security, and productivity (β = 0.648, p < 0.05). The study concluded that digital transformation plays a critical role in enhancing the efficiency, accountability, and overall performance of the Nigeria Immigration Service. It recommends sustained investment in online platforms, modernization of document processing systems, expansion of digital payment infrastructure, and strengthened inter-agency data integration to further improve service delivery and institutional effectiveness.